De novo exonic deletion of KDM6A in a Chinese girl with Kabuki syndrome: A case report and brief literature review. Issue 6 (30th March 2016) - Yang, Pu; Tan, Hu; Xia, Yan; Yu, Qian; Wei, Xianda; Guo, Ruolan; Peng, Ying; Chen, Chen; Li, Haoxian; Mei, Libin; Huang, Yanru; Liang, Desheng; et al.
Abstract : Kabuki syndrome (KS) is a rare condition with multiple congenital anomalies and mental retardation. Exonic deletions, disrupting the lysine (K)‐specific demethylase 6A ( KDM6A ) gene have been demonstrated as rare cause of KS. Here, we report a de novo 227‐kb deletion in chromosome Xp11.3 of a 7‐year‐old Chinese girl with KS. Besides the symptoms of KS, the patient also presented with skin allergic manifestations, which were considered to be a new, rare feature of the phenotypic spectrum. The deletion includes the upstream region and exons 1–2 of KDM6A and potentially causes haploinsuffiency of the gene. We also discuss the mutation spectrum of KDM6A and clinical variability of patients with KDM6A deletion through a literature review. © 2016 Wiley Periodicals, Inc.